الزواج السري بين القبائل الصومالية في كينيا: دراسة فقهية ميدانية - Gure, Halima Hamdi; Ghalia, Bouhedda; Ibrahim Mohamed, Hossam El Din (IIUM Press, 2022)
This research aims to shed lights on the different types of marriage prevalent among the ethnic Somalians living in Kenya and describe their concepts to understand the extent of their conformity or non-conformity with the terms and conditions of a valid marriage in Sharīʽah. Additionally, it discusses the related views and proofs of the jurists. The problem lies in the increase of the phenomenon of secret marriage among the Somalian community in Kenya recently and lack of focus on the importance of legal marriage. This problem needs scientific research, to protect the marital relationship from disintegration. The research adopts the inductive approach, the analytical method, and the field study for collecting all information and data relevant to the topic and for explaining the types of secret marriage. The research concludes with several results, the most important of which is that any type of secret marriage will not be considered as legally valid, except if it conforms to the terms and conditions of the Sharīʽah, established by the jurists based on the texts of the Holy Qur’ān and Sunnah; and wherever, these conditions are missed, the marriage will not be considered as legally valid.